The commercialisation of multi-supplier frameworks in the UK public sector: the divergence between law and practice - Brunning, Steven (2024)
Public procurement rules that specifically regulate public sector framework agreements only came into force in the UK in 2006. These implement EU directives, the most recent being Directive 2014/24/EU transposed in the Public Contracts Regulations 2015. The EU rules are skeletal in nature as they are intended to apply across all EU Member States. The UK Government has historically taken a light touch approach to implementing the EU directives, reserving significant discretion to contracting authorities rather than setting out detailed, prescriptive rules. The lack of regulatory controls and detailed guidance on the establishment, management and use of frameworks has led to the development of a competitive framework market in the UK and the adoption of commercial behaviours by central purchasing bodies seeking to attract business to their frameworks. This has resulted in some questionable consequences from a legal and commercial perspective that require investigation. It is concluded that the commercialisation of frameworks has led to fundamental disconnects between the law and practice, calling into question the relevance and efficacy of current regulatory policy and the practical effectiveness of the framework tool.